2007
DOI: 10.1111/j.1439-037x.2007.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium Silicate on Growth, Physiological Parameters and Mineral Nutrition in Two Legume Species Under Salt Stress

Abstract: Cowpea and kidney bean plants were grown in a hydroponic system, and the effect of calcium silicate supplied to the nutrient solution under salt stress was investigated. The plants were subjected to four different treatments: (1) nutrient solution alone (C), (2) nutrient solution + 40 mmol l )1 NaCl (NaCl), (3) nutrient solution + 40 mmol l )1 NaCl + 0.5 mmol l )1 CaSiO 3 (NaCl + Si 1 ) and (4) nutrient solution + 40 mmol l )1 NaCl+1 mmol l )1 CaSiO 3 (NaCl + Si 2 ). The results showed that, in both species, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 52 publications
0
55
0
4
Order By: Relevance
“…K and Ca had more important roles than Mg for seed yield improving in saline environment. The importance of shoot ions including Ca and K than Na for seed yield improving of Brassica species were emphasized in the other studies (Volkamar, 1998;Munnus, 2002;Murillo-Amador et al, 2007). DSM12 had the highest amount of K and also its S/C ratio.…”
Section: Genetic Variations For the Traitsmentioning
confidence: 91%
See 2 more Smart Citations
“…K and Ca had more important roles than Mg for seed yield improving in saline environment. The importance of shoot ions including Ca and K than Na for seed yield improving of Brassica species were emphasized in the other studies (Volkamar, 1998;Munnus, 2002;Murillo-Amador et al, 2007). DSM12 had the highest amount of K and also its S/C ratio.…”
Section: Genetic Variations For the Traitsmentioning
confidence: 91%
“…Although other shoot cation concentrations were decreased at high salinity level, Cl concentration was increased (Table 3). In previous studies (Volkamar, 1998;Munnus, 2002;Murillo-Amador et al, 2007) it was concluded that in response to salinity stress, endogenous Na concentration increased in the various Brassica genotypes whereas K concentration decreased.…”
Section: Effects Of Salinity Levels On the Traitsmentioning
confidence: 94%
See 1 more Smart Citation
“…It seems that Si alleviates salinity induced stress on growth of soybean by improving photosynthesis and transpiration rates, as drastic decline in photosynthesis and transpiration was caused by salt stress in cowpea, kidney bean(Murillo- Amador et al 2007) and bush bean…”
mentioning
confidence: 99%
“…Furthermore, salinity-induced reduction in water and K + uptake by plants usually interfered with cell division and/or extension because of reduced turgor, leading to reduced plant growth and development (Ashraf et al, 2008). Addition of plant mineral nutrients through soil or foliar spray could provide protective mechanisms against salinity stress (Kaya et al, 2007;Murillo-Amador et al, 2007;Ashraf et al, 2012;Ashraf et al, 2015b). It was found that application of additional K (K 50 and K 100 ) to salt-stressed medium (NaCl 100 and NaCl 180 ) reduced the uptake of Na These findings were contradicted to earlier research which reported that higher K application in saline environment hastened the deleterious impacts of salinity on plant growth causing severe decline in plant growth and development in sorghum (Sorghum bicolor L.) under salt stress (Jafari et al, 2009).…”
Section: Discussionmentioning
confidence: 99%